Critical mathematical thinking ability of junior high school students viewed from cognitive style - A'yun, Qurrota; Handayani, Luluk; Sujiwo, Dimas Anditha Cahyo (International Journal of Trends in Mathematics Education Research, 2025)
This study aims to analyze students' critical thinking skills in solving Two-Variable Linear Equations (PLDV) problems based on reflective and impulsive cognitive styles. The subjects of the study consisted of four students, namely two reflective students (SR1 and SR2) and two impulsive students (SI1 and SI2). This study used a qualitative method with a case study approach. We obtained data through critical thinking tests, in-depth interviews, and analysis of student answer documents. The results showed that reflective students could do all four types of critical thinking: interpretation, analysis, evaluation, and inference. They were also able to give correct and organized answers. In contrast, impulsive students only fulfilled some of the indicators, tended to answer quickly, and made mistakes in analyzing and verifying answers. The main factor influencing this difference was the more careful problem-solving approach in reflective students compared to impulsive students. Based on these findings, it is recommended that learning strategies be adjusted to students' cognitive styles, for example, through reflection-based learning and group discussions to improve critical thinking skills. Thus, this study contributes to the development of learning methods that are more adaptive to students' cognitive characteristics in understanding and solving mathematical problems.